Numerical simulation of 4-turns nitrogen pulsating heat pipe. (April 2019) - Li, M.N.; Wu, Z.X.; Xu, D.; Li, L.F.
Abstract: In the present study, an investigation of temperature and pressure behavior in a two-dimensional closed-loop pulsating heat pipe (PHP) in vertical bottom heating mode has been carried out numerically. Nitrogen was used as working fluid in this 4-turns PHP. Structured meshing configuration has been used and Volume of Fluid (VOF) method has been employed for the two-phase flow simulation. Constant heat flux and constant temperature boundary conditions have been applied for the evaporator and the condenser sections, respectively. The initial condition was set as 0.5 liquid volume fraction and 77 K in every cell. Under the combined function of gravity and surface tension, pure liquid and vapor phase were produced, and the random liquid slugs and vapor bubbles distribution was formed. The temperature oscillation of every channel in evaporator and condenser sections was obtained and analysed.